Penerbitan Izin Edar Kosmetika Melalui Online Single Submission Risk-Based Approach Pasca Berlakunya Undang-Undang Cipta Kerja - Farina Firda Eprilia; Adrian E. Rompis; Dicky Risman (Manabia: Journal of Constitutional Law, 2022)
This study aims to find out the comparison of the licensing system for cosmetics distribution before and after the Job Creation Law was formed and the implications for legal protection for cosmetics business actors, consumers and the public. This study uses empirical juridical methods, based on primary data and secondary data. The results of the study show that after the entry into force of the Job Creation Law there has been a reform of the licensing climate through updating the Online Single Submission system to an Online Single Submission-Risk Based Approach. The consideration for issuing a distribution license for cosmetics is based on the risks arising from the type of business concerned and adjusted to the content of cosmetic pharmaceutical preparations. Procedurally, this latest regulation provides convenience for business actors in obtaining a permit. Nevertheless, practically a system that tends to be early also raises various problems for both related agencies/institutions and business actors.